Gender dynamics in watermelon farming in Ijebu-North Local Government Area, Ogun State - Taiwo, A. M.; Bamgbowu, S. A.; Samuel, J. E. (ADAN JOURNAL OF AGRICULTURE, 2025)
This study investigated the gender roles in the production of watermelon in Ijebu North local government area of Ogun State. Using a two-stage sampling procedure, 120 respondents were randomly sampled and interviewed. Data were analyzed using frequency counts, percentages, mean, standard deviation and t-test. Results indicated that male had access mostly to seeds ( ̅ = 3.43±0.76) and farm labour ( ̅ = 3.36±0.72) while female had access mostly to seeds ( ̅ = 3.52±0.51), herbicides and fertilizers ( ̅ = 3.24±0.74). The male farmers were more involved building repairs ( ̅ = 2.02±0.73) and home sanitation ( ̅ = 2.00±0.75) while the women were more involved in food preparation ( ̅ = 2.93±0.26) and child care ( ̅ = 2.79±0.56). Constraint faced by male farmers were transportation ( ̅ = 2.29±0.58) and poor pricing of produce ( ̅ = 2.54±0.58) while the females faced poor pricing of produce ( ̅ = 2.69±0.47) and high incidence of pest and disease attack ( ̅= 2.48±0.63). The results further showed that male farmers were mostly involved in seed selection ( ̅ = 2.64±0.59) and fertilizer application ( ̅ = 2.58±0.60) while the female farmers were mostly involved in seed selection ( ̅ = 2.83±0.38) and marketing ( ̅ = 2.86±0.35). The findings showed a significant difference in harvesting (t = 0.04; p< 0.05) and marketing (t = 0.00; p< 0.05) roles of the respondents in watermelon production operations. The study concluded that both male and female farmers participated in watermelon farming and household tasks. The study recommended fostering gender-specific agricultural policies and programmes to enhance productivity and equity